2020
DOI: 10.1016/j.jhep.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

aMAP risk score predicts hepatocellular carcinoma development in patients with chronic hepatitis

Abstract: Background & Aims: Hepatocellular carcinoma (HCC) is the leading cause of death in patients with chronic hepatitis. In this international collaboration, we sought to develop a global universal HCC risk score to predict the HCC development for patients with chronic hepatitis. Methods: A total of 17,374 patients, comprising 10,578 treated Asian patients with chronic hepatitis B (CHB), 2,510 treated Caucasian patients with CHB, 3,566 treated patients with hepatitis C virus (including 2,489 patients with cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
210
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 205 publications
(254 citation statements)
references
References 22 publications
4
210
2
2
Order By: Relevance
“…However, the 3-year cumulative incidence of HCC was 1.5% and 4.8%, and the 5-year cumulative incidence of HCC was 8.1% and 19.9% in patients classified into the intermediate-risk (50-60 points) and high-risk (60-100 points) groups, respectively. However, this study found that low-risk patients accounted for 45%, while the highrisk patients accounted for only 17.9% of all non-viral HCC [85] . Therefore, the role of the aMAP model in identifying high-risk patients for development of HCC in patients with non-viral liver disease needs further evaluation.…”
Section: Family History Of Liver Cancercontrasting
confidence: 61%
“…However, the 3-year cumulative incidence of HCC was 1.5% and 4.8%, and the 5-year cumulative incidence of HCC was 8.1% and 19.9% in patients classified into the intermediate-risk (50-60 points) and high-risk (60-100 points) groups, respectively. However, this study found that low-risk patients accounted for 45%, while the highrisk patients accounted for only 17.9% of all non-viral HCC [85] . Therefore, the role of the aMAP model in identifying high-risk patients for development of HCC in patients with non-viral liver disease needs further evaluation.…”
Section: Family History Of Liver Cancercontrasting
confidence: 61%
“…Fan R et al. built a prediction model which incorporates ALBI score to predicts HCC development in patients with chronic hepatitis ( 49 ). This model was developed based on more than 17,000 patients from 11 global prospective studies and yielded a C-index of 0.82–0.87.…”
Section: Discussionmentioning
confidence: 99%
“…Ding M et al found that ALBI grade is an independent risk factor for overall survival in patients with HCC after thermal ablation (48). Fan R et al built a prediction model which incorporates ALBI score to predicts HCC development in patients with chronic hepatitis (49). This model was developed based on more than 17,000 patients from 11 global prospective studies and yielded a C-index of 0.82-0.87.…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively assessed the diagnostic performance of five validated HCC risk scores, namely: Guide with Age, Gender, HBV DNA, core promotor mutations and cirrhosis score (GAG HCC score), 10 Risk estimation for hepatocellular carcinoma in Chronic Hepatitis B (REACH B score), 11 Modified REACH B score (HBV DNA substituted for liver fibrosis measurements), 12 modified platelets, age, gender (mPAGE B score) 13 and the age‐Male‐ALBI‐Platelets (aMAP) score 14 …”
Section: Methodsmentioning
confidence: 99%